Strategi Peningkatan Tingkat Hunian Melalui Promosi, Kualitas Layanan, dan Citra Hotel di Bali Mega Hotel Jimbaran - Yoga, Putu Lina Kurnia; Maheswari, Anak Agung Istri Agung; Nurmalasari, Made Ratih; Muna, Nilna (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study examines how promotional strategies, service quality, and hotel image influence occupancy rates at Bali Mega Hotel Jimbaran. The research involved 98 respondents living in the South Kuta area, aged 17–45 years, who had stayed at the hotel more than once. Data were analyzed using Partial Least Square (PLS) version 4. The findings indicate that all three variables—promotional strategies, service quality, and hotel image—positively and significantly contribute to higher occupancy levels. These results highlight the importance of strengthening the hotel’s marketing efforts, particularly through engaging digital promotions that appeal to potential guests. In addition, improving service quality by enhancing staff responsiveness, refining guest interaction, and ensuring consistent service delivery is essential. The study also recommends upgrading outdated facilities, adding amenities that guests commonly expect, and ensuring greater comfort throughout the hotel environment. Collectively, these improvements can enhance the hotel’s overall image, align more closely with guest expectations, and ultimately increase the value perceived by tourists, thereby helping Bali Mega Hotel Jimbaran remain competitive in the hospitality market.